PENERAPAN MODEL PEMBELAJARAN JIGSAW MODIFIKASI UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI PESERTA DIDIK KELAS XII MIPA 3 SMA NEGERI 1 KUTA UTARA - Sarlince Danga Nani; I Wayan Sumandya (Widyadari, 2023)
This study aims to improve biology learning outcomes of SMA Negeri 1 Kuta Utara students through the application of a modified jigsaw cooperative learning model. This research method uses Classroom Action Research (PTK) which is carried out in two cycles with each cycle consisting of planning, implementing actions, observing and reflecting. The subjects of this study were students of class XII MIPA 3 SMA Negeri 1 North Kuta with a total of 37 students. This study uses a description test instrument on the Mutations material. Data collection is carried out by giving a description test independently to see the learning outcomes of students. The results showed that there was an increase in student learning outcomes. In cycle I, the average percentage obtained was 67.86% in the complete category. The number of students included in the complete category was 25 people. In the second cycle, the average percentage obtained was 86.48% in the complete category. The number of students included in the complete category was 32 people. Based on the results of this study, it can be concluded that the application of the modified jigsaw learning model can improve the learning outcomes of class XII MIPA 3 students at SMA Negeri 1 Kuta Utara.